Lack of mucosal cholinergic innervation is associated with increased risk of enterocolitis in Hirschsprung’s disease - Keck, Simone; Galati-Fournier, Virginie; Kym, Urs; Moesch, Michèle; Usemann, Jakob; Müller, Isabelle; Subotic, Ulrike; Tharakan, Sasha J.; Krebs, Thomas; Stathopoulos, Eleuthere; Schmittenbecher, Peter; Cholewa, Dietmar; et al. (Cellular and Molecular Gastroenterology and Hepatology, 2021)
Background & Aims - Hirschsprung’s disease (HSCR) is a congenital intestinal motility disorder defined by the absence of enteric neuronal cells (ganglia) in the distal gut. The development of HSCR-associated enterocolitis remains a life-threatening complication. Absence of enteric ganglia implicates innervation of acetylcholine-secreting (cholinergic) nerve fibers. Cholinergic signals have been reported to control excessive inflammation, but the impact on HSCR-associated enterocolitis is unknown. - Methods - We enrolled 44 HSCR patients in a prospective multicenter study and grouped them according to their degree of colonic mucosal acetylcholinesterase-positive innervation into low-fiber and high-fiber patient groups. The fiber phenotype was correlated with the tissue cytokine profile as well as immune cell frequencies using Luminex analysis and fluorescence-activated cell sorting analysis of colonic tissue and immune cells. Using confocal immunofluorescence microscopy, macrophages were identified in close proximity to nerve fibers and characterized by RNA-seq analysis. Microbial dysbiosis was analyzed in colonic tissue using 16S-rDNA gene sequencing. Finally, the fiber phenotype was correlated with postoperative enterocolitis manifestation. - Results - The presence of mucosal nerve fiber innervation correlated with reduced T-helper 17 cytokines and cell frequencies. In high-fiber tissue, macrophages co-localized with nerve fibers and expressed significantly less interleukin 23 than macrophages from low-fiber tissue. HSCR patients lacking mucosal nerve fibers showed microbial dysbiosis and had a higher incidence of postoperative enterocolitis. - Conclusions - The mucosal fiber phenotype might serve as a prognostic marker for enterocolitis development in HSCR patients and may offer an approach to personalized patient care and new therapeutic options.
Gesehen am 18.10.2021